Finance theory and asset pricing - Milne, Frank (Oxford University Press, 2003)
Finance Theory and Asset Pricing provides a concise guide to financial asset pricing theory for economists. Assuming a basic knowledge of graduate microeconomic theory, it explores the fundamental ideas that underlie competitive financial asset pricing models with symmetric information. Using finite dimensional techniques, this book avoids sophisticated mathematics and exploits economic theory to clarify the essential structure of recent research in asset pricing. In particular, it explores arbitrage pricing models with and without diversification, Martingale pricing methods and representative agent pricing models; discusses these ideas in two-date and multi-date models; and provides a range of examples from the literature. This second edition includes a new section dealing with more advanced multi-period models. In particular it considers discrete factor structure models that mimic recent continuous time models of interest rates, money, and nominal rates and exchange rates. Additional sections sketch extensions to real options and transaction costs